PENGARUH PENGGUNAAN CAPCUT TERHADAP KEBEBASAN BEREKSPRESI MAHASISWA INDONESIA DI MEDIA SOSIAL - Ratu Prameswari Iltizam; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study examines CapCut usage and its influence on students’ freedom of expression on social media. Freedom of expression refers to confidence, the courage to express ideas, and satisfaction in self-expression. A quantitative descriptive-associative design was used with 100 purposively selected respondents, and data were collected through a Likert-scale questionnaire. Analysis was conducted using simple linear regression. The findings show that editing feature convenience (X1), duration and frequency of use (X2), and usage purpose (X3) have a positive and significant effect on students’ freedom of expression (p < 0.05). The strongest effect appears in the relationship between usage purpose and satisfaction in self-expression (β = 0.640). Regression results indicate that CapCut usage explains 33.1% of the variance in freedom of expression (R² = 0.331). Keywords: CapCut, Freedom of Expression, Social Media, Digital Self-Expression.